A global sensitivity study of cyclohexane oxidation under low temperature fuel-rich conditions using HDMR methods - Ziehn, T.; Hughes, K. J.; Griffiths, J. F.; Porter, R.; Tomlin, A. S. (Combustion theory and modelling, 2009)
This paper presents a global sensitivity analysis of simulations of low-temperature isothermal cyclohexane oxidation under fuel-rich conditions using the method of high-dimensional model representation (HDMR). The analysis is used to investigate the important features of the oxidation process, as well as possible factors underlying qualitative discrepancies between simulations and experiments. The particular feature of interest is the characteristic of quadratic autocatalysis, which is observed experimentally and leads to the maximum rate of reaction occurring at 50% consumption of the deficient reactant (oxygen), with the fuel consumption exerting only a weak dependence. The kinetic mechanisms tested do not exhibit this characteristic when simulating the experimental conditions. The models also exhibit shorter induction times than those observed in the experiment. The HDMR study demonstrates a sensitivity of these features to the A-factors of key reactions of the cyclohexylperoxy radical (C 6 H 11 OO). At the low temperatures studied here, these are peroxy-peroxy radical reactions rather than the isomerisation routes that have been the subject of other investigations at higher temperatures. The low temperature product channels for reactions of the cyclohexylperoxy radical are therefore an important area for future kinetic studies. The effects of wall reactions of peroxy and peroxide species were not found to outweigh the impact of the main A-factors, but including wall losses led to significant higher order interactions between input parameters. This constitutes an interesting and important area for further research.